Treating acute pain with ossicodone/naloxone in Intensive Care Unit: case report of lower limbs compartment syndrome - Antonio Galzerano; Chiara Merenda; Elena Sabatini; Alessio Trabalza; Nadia Dentini; Vito Aldo Peduto (Publiediting, 2014)
Since its introduction in the Italian market, oxycodone/naloxone has been used in the treatment of pain in an exclusive use of non-ICU patients, mainly due to its oral formulation. In critically ill patients undergoing infusive analgesic-sedation in ICU the drug is strongly affected by the abolition of swallowing reflex. We describe the case of a patient with lower limbs compartment syndrome by direct trauma with a rapid switch on third day of hospitalization from analgesic sedation using propofol-remifentanil to oxycodone/naloxone and pregabalin.